Community Assistance in the Post-Pandemic Period through the Application of Appropriate Technology in an Effort to Realize an Energy Independent Village Based on Healthy Livestock - Hery Sumasto (Frontiers in Community Service and Empowerment, 2022)
This community service aims to provide assistance to the people of Gonggang Village, Poncol District, Magetan Regency, during the post-pandemic period through the application of science and technology according to community needs in an effort to create an energy independent village based on healthy livestock. The main problems faced by the people of Gonggang Village due to the lengthy period of the Pandemic are the economic downturn, the low quality of public health, and the unmonitored development of children under five. Communities are required to have economic resilience in meeting their needs to survive. The presence of academics in the community is carried out by applying Appropriate Technology, so that people have a quality, healthy and productive life. Community Assistance in the Post- Pandemic Period is carried out through the application of appropriate technology based on community needs, carried out through the application of Appropriate Technology to Utilize Cattle Manure as a source of energy/Biogas. With the implementation of appropriate technology, it is hoped that a healthy village, independent of energy based on healthy livestock, can be achieved, because it has obtained an alternative energy source for LPG. This Community Service is carried out with the following methods: training, coaching, Focus Group Discussion (FGD), practicum, modeling and mentoring for 6 months. Strategy for achieving goals by: 1) classical material 2) field practice 3) follow-up implementation. Cooperation: This Community. Service activity is a collaboration between 3 (three) Poltekkes, namely Poltekkes Semarang, Poltekkes Malang and Poltekkes Surabaya. The total time for the implementation of the activity is 6 months. Outputs: 1) Publication; 2) publication through mass media; 3) Intellectual Property Rights.